2022
DOI: 10.1111/geb.13599
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated invasion through the evolution of dispersal behaviour

Abstract: Aim The continuous spread of invasive species is attributed to demographic processes and high dispersal rates. Both can change and evolve during range expansion, eventually accelerating spread dynamics. Here, we document such an accelerated spread for one of the most invasive spiders in Europe, the dwarf spider Mermessus trilobatus, and test whether dispersal, reproduction or competitive ability is at the source of this pattern. Location Europe. Time period 1981–2021. Major taxon studied Mermessus trilobatus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 145 publications
1
6
0
Order By: Relevance
“…Previously several research, both theoretically and empirically, have demonstrated that indeed dispersal properties of a species can evolve rather rapidly under such congenial conditions (McPeek & Holt 1992;Hutson et al 2003;Fronhofer et al 2014;Tung et al 2018b). This evolution of greater dispersal properties can lead to a species becoming invasive, as is the case with Cane toads in Australia (Phillips et al 2008;Shine et al 2021) and dwarf spiders in Europe (Narimanov et al 2022), and pose a threat to native ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously several research, both theoretically and empirically, have demonstrated that indeed dispersal properties of a species can evolve rather rapidly under such congenial conditions (McPeek & Holt 1992;Hutson et al 2003;Fronhofer et al 2014;Tung et al 2018b). This evolution of greater dispersal properties can lead to a species becoming invasive, as is the case with Cane toads in Australia (Phillips et al 2008;Shine et al 2021) and dwarf spiders in Europe (Narimanov et al 2022), and pose a threat to native ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…2008; Shine et al . 2021) and dwarf spiders in Europe (Narimanov et al . 2022), and pose a threat to native ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unclear what factors are driving the spread of D. graecus . Narimanov et al (2022) demonstrated that the invasive linyphiid Mermessus trilobatus (Emerton, 1882), originating from North America, benefits from high dispersal behavior, which appears to be the main driver of its rapid spread. However, this does not appear to be the primary factor driving the current spread of D. graecus .…”
Section: Discussionmentioning
confidence: 99%
“…Especially other agrobiont linyphiid species exhibiting activity during winter like Centromerita bicolor (Blackwall, 1833) (Blick et al 2003, Schaefer 1977), may be potentially affected. However, it is worth noting that the comparably sized M. trilobatus has invaded and established in similar habitats without having (measurable) negative effects on the local ecosystem until now (Eichenberger et al 2009, Narimanov et al 2021, 2022, De Smedt & Van Keer 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Today it can be found in every larger collection from any open habitat. Current overviews are given in Hirna (2017) and Narimanov et al (2022). In our investigation, the species was found in 28 sites on 15 buildings.…”
Section: New Species For the Swiss Faunamentioning
confidence: 99%